An Unusual Presentation of Congenital Heart Disease - Goswami, Nilesh J. (2003)
We describe an unusual presentation of congenital heart disease mimicking preeclampsia in a young, gravid girl. The diagnosis of Shone's complex was confirmed by echocardiography. This complex is manifested by multiple levels of obstruction involving the left side of the heart and the systemic circulation. It is extremely rare, especially in pregnant adolescents. We briefly describe the patient's clinical history, physical examination, and treatment, as well as our clinical decisions regarding her case. The discussion focuses on the spectrum of findings in Shone's complex and the physiologic impact of therapy on this patient. (Tex Heart Inst J 2003;30:214–7)